Repetitive Pain in Neonatal Male Rats Impairs Hippocampus-Dependent Fear Memory Later in Life - Xia, Dongqing; Min, Cuiting; Chen, Yinhua; Ling, Ru; Chen, Mengying; Li, Xiaonan (Frontiers in Neuroscience, 2020)
Preterm infants in neonatal intensive care units are inevitably subjected to numerous painful procedures. However, little is known about the consequences of early pain experience on fear memory formation later in life. We hypothesized that exposure to repetitive pain in early life triggered hippocampal synaptic plasticity and resulted in memory deficiency in prepubertal and adult rats. From the day of birth (P0) to postnatal day 7 (P7), neonatal male rat pups were randomly assigned to either needle pricks or tactile touches repetitively every 6 h. Trace fear conditioning was performed on rats on P24–P26 and P87–P89. On P24 and P87, rats were sacrificed for molecular and electrophysiological studies. On P24–26 and P87–89, rats that experienced neonatal needle treatment showed a significant reduction in freezing time in the contextual fear conditioning (P < 0.05) and trace fear conditioning tests (P < 0.05). Moreover, repetitive neonatal procedural pain caused a significant decrease in the magnitude of hippocampal long-term potentiation induced by high-frequency stimulation. Furthermore, rats that experienced neonatal needle treatment demonstrated sustained downregulation of NR1, NR2A, NR2B, and GluR1 expression in the hippocampus. Therefore, neonatal pain is related to deficits in hippocampus-related fear memory later in life and might be caused by impairments in hippocampal synaptic plasticity.